Genetic Diversity of Porcine Group A Rotavirus Strains from Pigs in South Korea - Gyu-Nam Park; Da In Kim; SeEun Choe; Jihye Shin; Byung-Hyun An; Ki-Sun Kim; Bang-Hun Hyun; Jong-Soo Lee; Dong-Jun An (Viruses, 2022)
Porcine group A rotavirus (PoRVA; family, Reovirideae) strains cause acute viral gastroenteritis in piglets (especially suckling and weaned pigs), resulting in significant economic losses. In this study, we analyzed the VP7 and VP4 genes of PoRVA isolated between 2014 and 2018 from domestic pigs in South Korea to investigate the prevalence of predominant circulating genotypes (G and P types). The prevalence of the PoRVA antigen in the diarrheic fecal samples was 14.1% (53/377). Further genetic characterization of the VP7 and VP4 genes of 53 PoRVA isolates identified six different G-genotypes and five different P genotypes. The G4 and G9 genotypes were the most common (each 39.6%) in PoRVA-positive pigs, followed by P[7] and P[6] (33.9% and 30.1%, respectively). Because the G5 and G9 genotype vaccines are currently mainly used in South Korea, this result provides valuable epidemiological information about the genetic characteristics of PoRVA circulating on domestic pig farms. Development of a novel PoRVA vaccine that targets the current strains circulating in South Korea may be required for more effective virus control on pig farms.